Induced moments and lateral deflections in columns with initial imperfections and semirigid connections: ii) verification and examples (2012)
An analytical method and the closed-form expressions derived in a companion paper are used to evaluate the induced elastic bending moments and second-order deflections in slender prismatic columns with initial geometric imperfections (i.e., initial curvature and out-of-plumbness) and semirigid connections when the columns are subjected to eccentric axial loads at both ends. Comparisons of the induced elastic moments, the second-order deflections, and the critical loads obtained using the proposed approach, and those available in the technical literature for classic column cases are presented herein. Also, sensitivity studies and several examples are presented in detail which demonstrate the effectiveness and accuracy of the proposed closed-form equations and the importance of initial imperfections, semirigid connections, and lateral bracing on the second-order behavior and stability of beam-columns. Results obtained from the proposed equations are compared with those obtained using the FEM computer program ABAQUS, showing its simplicity and accuracy. The closed-form expressions can be used by researchers and structural engineers to investigate the effects of initial imperfections and semirigid connections on the elastic behavior of columns under heavy eccentric axial loads, including cases with relatively large deflections ( and lt; 0.1 times the column span).